Diagnosis and treatment of cryptorchid testicular torsion in children: A 12-year retrospective study - Chen, Pengyu; Yang, Zhilin; Chen, Nana; Liu, Lei; Su, Jiahong; Sun, Mengkui; Li, Shoulin (Frontiers in Pediatrics, 2022)
Purpose To investigate the clinical characteristics, treatment, and prognosis of cryptorchid testicular torsion in children. Methods The clinical data of 25 children who received treatment for cryptorchid testicular torsion between January 2010 and December 2021 were retrospectively reviewed. The median age of the patients was 64.5 months (range: 2 months to 15 years). All patients had unilateral torsion, and the duration of symptoms ranged from 3 to 192 h. Results Among the 25 patients, five underwent orchidopexy, while the remaining 20 underwent orchiectomy. After 6 months to 8 years of follow up, the 20 patients who had undergone orchiectomy had a well-developed testis on the healthy side. Four of the five patients who had undergone orchidopexy of the affected testis had well-developed testes bilaterally, while one experienced testicular atrophy. Conclusion Cryptorchid testicular torsion is a rare urological emergency that displays a delayed presentation and is often misdiagnosed. Clinicians need to carefully review the patient's medical history and ultrasound findings and perform a thorough physical examination to make a correct diagnosis. Active testicular exploration is required for patients suspected to have cryptorchid testicular torsion, and the decision to perform orchidopexy or orchiectomy depends on the intraoperative situation.